2020
DOI: 10.1111/bjh.16633
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐treatment metabolic tumour volume and total lesion glycolysis are superior to conventional positron‐emission tomography/computed tomography variables for outcome prediction in patients with newly diagnosed multiple myeloma in clinical practice

Abstract: Metabolic tumour volume (MTV) and total lesion glycolysis (TLG) are positron-emission tomography/computed tomography (PET/CT) variables for predicting multiple myeloma's (MM) outcome. We retrospectively investigated and compared the predictive value of MTV, TLG and high-risk PET/CT variables in clinical practice in 185 patients with newly diagnosed symptomatic MM. High-risk PET/CT findings were defined as the presence of at least one of the following: more than three focal lesions, maximum standardised uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
0
25
1
Order By: Relevance
“…The presented automatic BM segmentation could be of use for a variety of subsequent analyses in the future, as for example automatic extraction of vertebral heights for fracture detection, or to define a search zone for a second algorithm to perform automatic detection or segmentations of all focal lesions within the BM. This could enable automatic, volumetric tumor load assessment, which would be of use for risk stratifications in (smoldering) MM 12–15 . The algorithmic concept can be transferred to other oncologic entities with disseminated skeletal involvement and to other imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The presented automatic BM segmentation could be of use for a variety of subsequent analyses in the future, as for example automatic extraction of vertebral heights for fracture detection, or to define a search zone for a second algorithm to perform automatic detection or segmentations of all focal lesions within the BM. This could enable automatic, volumetric tumor load assessment, which would be of use for risk stratifications in (smoldering) MM 12–15 . The algorithmic concept can be transferred to other oncologic entities with disseminated skeletal involvement and to other imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Wholebody metabolic tumor volume (MTV) and whole-body tumor lesion glycolysis (TLG) (i.e., MTVxSUV mean ) are promising prognostic markers showing superiority in comparison with the baseline number of FLs or baseline SUV max in a cohort of patients treated with chemotherapy comprising thalidomide, dexamethasone, cisplatin, cyclophosphamide, and etoposide, followed by intensification by melphalan, tandem autologous stem cell transplant (ASCT), and maintenance by thalidomide and dexamethasone (total therapy 3 protocol) (54). Similar results were found in a study of 185 NDMM patients treated with a proteasome inhibitor-based regimen (55).…”
Section: Baseline Imaging Techniques As Prognostic Factorsmentioning
confidence: 53%
“…The Chisquare test verified that the GEP and TLG are independent prognostic factors. Furthermore, they found that TLG > 205 g accurately divided ISS stage II patients into two subgroups with outcomes similar to those of ISS stage I and ISS stage III, respectively [22].…”
Section: Mtv and Tlgmentioning
confidence: 95%
“…Terao et al [22] utilized an absolute fixed threshold of SUV = 2.5 to calculate MTV and TLG from FDG-PET/CT images of NDMM patients. In a multivariate analysis, a high-burden MTV (>56.4 cm 3 ) had prognostic values for PFS and OS even when the model was adjusted for the R-ISS and high-risk FDG-PET findings.…”
Section: Mtv and Tlgmentioning
confidence: 99%
See 1 more Smart Citation